Nanoengineered mitochondria for mitochondrial dysfunction and anti-aging interventions - Deng, Siqi; Ren, Yingying; Zhang, Qian; Liu, Qinling; Long, Jiaxin; Picard, Kelsey; Martin, Miguel; Miller, Thomas; Yuan, Chaofan; He, Yunxiang; Guo, Junling (Frontiers in Aging, 2025)
Aging is a multifactorial process and a major risk factor for chronic disease. Among its hallmarks, mitochondrial dysfunction plays a central role, driven by impaired respiration and accumulated mitochondrial DNA mutations that disrupt energy metabolism and redox balance. Conventional mitochondrial transplantation has been explored as a therapeutic strategy, but its emphasis on increasing mitochondrial quantity without restoring function has limited success. Recent advances in nanoengineered mitochondria that integrate isolated mitochondria with functional nanomaterials, offer new opportunities to enhance organelle quality, boost metabolic activity, and achieve targeted delivery. Preclinical studies highlight their promise in cardiovascular, neurodegenerative, and other age-related disorders. In this mini-review, mitochondrial dysfunction in aging is first introduced, followed by the summary of rational designed strategies for engineering mitochondrial biohybrids and their emerging applications, and finally translational challenges are further discussed. By bridging materials science and mitochondrial therapy, nanoengineered mitochondria may represent a next-generation approach to anti-aging interventions.